Pengaruh Customer Experience Terhadap Revisit Intention di Wisata Kuliner Bunderan Perumnas Cibeber Kota Cilegon - Nadea Rafika Fikri; Meutia Meutia; Ahmad Bukhari (Pusat Unggulan Iptek Ketahanan Pangan Universitas Sultan Ageng Tirtayasa, 2020)
The purpose of this study is to analyze the influence between customer experience variables including physical environment, social interaction, accessibility, and emotional experience on variable revisit intention in culinary tour